Effect of Different Shade Levels on Growth and Yield Performances of Cauliflower. - Yasoda, P.G.C.; Pradheeban, L.; Nishanthan, K.; Sivachandiran, S. (International Journal of Environment, Agriculture and Biotechnology (IJEAB), 2018)
An experiment was conducted during March to July in 2017 (off season) at the Faculty of Agriculture, University of Jaffna, Ariviyal Nagar, Kilinochchi to study the effects of different shade levels on growth and yield performances of cauliflower. Different shade levels such as 25 % (open field), 50 % (single net house) and 75 % (double net house) were used as treatments. The experiment was conducted in completely randomized design (CRD) with four replications. Parametric (growth & yield) analysis were done by using SAS 9.1 package. The influence of environmental variables such as temperature, relative humidity and light intensity were also studied.The result revealed that growing of cauliflower in different shade levels showed great influence on plant growth and yield attributes. There were significant variations in number of leaves, plant height,curd weight, curd diameter and curd circumference of cauliflower under different light intensities. Light intensity in the shade net house was lower than in the open field. The highest vegetative growth and yield were observed in cauliflower which was grown in 50 % shade levels and the lowest yield was in 25 % shade level (open field). It can be concluded that cauliflower can be cultivated in 50 % shade levels successfully to produce quality curd during off season of the dry zone of Sri Lanka.
Keywords: Cauliflower; Growth; Shade levels; Yield